A facile and controllable synthesis of dual‐crosslinked elastomers based on linear bifunctional polydimethylsiloxane oligomers. Issue 23 (28th September 2016) - You, Yang; Huang, Weiyan; Zhang, Anqiang; Lin, Yaling
ABSTRACT: Dual‐crosslinked supramolecular elastomers with the hybrid network consisting of hydrogen bonds and covalent bonds combine the reversibility of hydrogen bond and mechanical properties of covalent crosslinking network. In this article, isocyanate mixture is used as curing agent to prepare dual‐crosslinked elastomer based on bifunctional polydimethylsiloxane under mild condition. This method can effectively build up a hybrid network with the designed structure. A series of elastomers with same hydrogen bond density and variable covalent crosslinking degree are obtained. Swelling measurements and 1 H‐NMR spectra confirm the feasibility and controllability of curing method, the increasing of bifunctional isocyanate give rise to higher covalent crosslinking degree, improving the solvent resistance. The studies on viscoelastic property show that the introduction of an irreversible covalent crosslinking network stabilize the hybrid network, restrain the chain movement. The mechanical and self‐healing property studies reveal that the covalent crosslink significantly reinforce the whole network, while the reparable strength seems to mainly depend on the hydrogen bond density. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 3760–3768 Abstract : A facile and effective strategy for preparing a dual‐crosslinked supramolecular elastomer is reported. Based on a previously neglected covalent crosslinking reaction during the preparation of the supramolecular elastomer, which is based on bifunctional carboxyl‐terminated polydimethylsiloxane (PDMS‐COOH2), an isocyanate mixture is introduced to cure the precursor into the supramolecular elastomer with hybrid crosslinking network. Thus a series of supramolecular elastomers with different covalent crosslink degrees can be easily synthesized just by adjusting the composition of curing agent.